Radicular and pseudoradicular pain symptoms - pathomechanisms of injury, diagnostics and therapy - Wioletta Jagucka-Mętel; Agata Baranowska; Tomasz Kubiak; Adam Figeland; Bartosz Żołnowski; Lidia Wrona-Żołnowska; Ewa Sobolewska (Rehabilitacja Medyczna, 2019)
Introduction: Pain localized within the lumbosacral spine, buttock, thigh, shank and foot may be radicular (discopathy and irritation of tissue structures) or pseudoradicular (dysfunctions of internal organs, scars, temporomandibular and sacroiliac joint disorders). Aim: In the study, we analyse symptoms of radicular and pseudoradicular origin, differentia-tion tests and therapeutic methods. Based on a review of subject-based literature, the mecha-nisms of intervertebral disc injury and the possibilities of their treatment have been presented. Methodology: Particular attention is paid to visceral therapy (visceral manipulation), consist-ing of work with the fascia and ligaments of internal organs, which eliminate disturbances of respiratory organ mobility, pain symptoms affecting specific points of the organ and restore proper alignment as well as function of internal organs. Results and conclusions: The complex system of anatomic-functional connections between the viscera and the spine causes the mutual interaction of these structures. Therefore, depend-ing on the type of pathology, a therapist, using osteopathic knowledge, works with organs directly connected with the disrupted segment of the spine.